Training and Education for Dental Professionals on Tobacco Cessation - Vishakha Rani; Ritesh Khosla; Rohini Sharma; Somanath R. Kunsi; Thara Chandran; Anzil K. S. Ali (Journal of Pharmacy and Bioallied Sciences)
Background: Tobacco use remains a major public health issue, contributing to numerous oral and systemic diseases. Dental professionals are in a unique position to offer tobacco cessation support, yet many lack adequate training and education in this area. This study evaluates the impact of a comprehensive training program on the knowledge, attitudes, and practices of dental professionals regarding tobacco cessation. Materials and Methods: A total of 150 dental professionals from various dental clinics participated in a six-month training program. The program included workshops, online modules, and practical sessions focused on tobacco cessation techniques, motivational interviewing, and patient education. Pre- and post-training surveys were administered to assess changes in knowledge, confidence, and frequency of tobacco cessation counseling. Data were analyzed using paired t-tests and Chi-square tests. Results: The training program significantly improved the participants’ knowledge of tobacco cessation (mean score increased from 60% to 85%, P < 0.001) and their confidence in providing cessation counseling (mean confidence rating increased from 3.2 to 4.5 on a 5-point scale, P < 0.001). Additionally, the frequency of tobacco cessation interventions in dental practices increased by 40% post-training (P < 0.05). Conclusion: Comprehensive training and education programs can substantially enhance the ability of dental professionals to support tobacco cessation. Such initiatives not only improve the knowledge and confidence of dental practitioners but also lead to more frequent and effective tobacco cessation interventions in clinical practice.